2015
DOI: 10.1093/nar/gkv1112
|View full text |Cite
|
Sign up to set email alerts
|

Tim/Timeless, a member of the replication fork protection complex, operates with the Warsaw breakage syndrome DNA helicase DDX11 in the same fork recovery pathway

Abstract: We present evidence that Tim establishes a physical and functional interaction with DDX11, a super-family 2 iron-sulfur cluster DNA helicase genetically linked to the chromosomal instability disorder Warsaw breakage syndrome. Tim stimulates DDX11 unwinding activity on forked DNA substrates up to 10-fold and on bimolecular anti-parallel G-quadruplex DNA structures and three-stranded D-loop approximately 4–5-fold. Electrophoretic mobility shift assays revealed that Tim enhances DDX11 binding to DNA, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 54 publications
(82 reference statements)
5
81
0
Order By: Relevance
“…This analysis indicated that most of the genes co-expressed with CONCR (correlation value > 0.45) encode for proteins known to be involved in DNA replication and chromosome maintenance (Figures S2F and S2G and Table S4), including DDX11 and several of its interacting partners, such as TIMELESS (Calì et al, 2016), ESPL1, and components of the minichromosome maintenance complex (MCM) (Figure S2H). This, together with the known function of DDX11 in sister chromatid cohesion, prompted us to investigate the functional role of CONCR in this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis indicated that most of the genes co-expressed with CONCR (correlation value > 0.45) encode for proteins known to be involved in DNA replication and chromosome maintenance (Figures S2F and S2G and Table S4), including DDX11 and several of its interacting partners, such as TIMELESS (Calì et al, 2016), ESPL1, and components of the minichromosome maintenance complex (MCM) (Figure S2H). This, together with the known function of DDX11 in sister chromatid cohesion, prompted us to investigate the functional role of CONCR in this process.…”
Section: Resultsmentioning
confidence: 99%
“…DDX11 is a DNA helicase that links the replication of the lagging DNA strand with the establishment of chromosomal cohesion (Bharti et al, 2014), and it is especially required in order to solve stalled replication forks (Calì et al, 2016). Although we cannot exclude that CONCR has additional activities, our results show that CONCR mainly functions at this level.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, co-immunoprecipitation experiments show that neither region is required for binding the DDX11 helicase ( Supplementary Fig. 5), a known binding partner of Timeless and whose ability to unwind G4s is stimulated by Timeless 36 . These results indicate that the C terminus of the Timeless protein has an important role in G4 replication with the DBD and the PDB both contributing to that function independently of DDX11 recruitment.…”
Section: The Timeless C-terminus Is Crucial For Processive G4 Replicamentioning
confidence: 99%
“…Although Timeless itself does not appear to possess a catalytic activity that would process DNA secondary structures, it interacts with the helicase DDX11 36 . DDX11 (or CHLR1) is a 5'-3' Fe-S helicase and belongs to the same superfamily 2 as FANCJ, RTEL and XPD 3 .…”
mentioning
confidence: 99%
“…In yeast, sister chromatid cohesion (which involves the ortholog of human ChlR1/DDX11 [83,84]) is coupled with lagging strand processing [103,104] and involves Ctf4 recruitment of Chl1 to the replisome [105], suggesting that DDX11 interactions with replisome-associated proteins [e.g. Flap Endonuclease 1 (FEN-1) [94] and Timeless [106]] are important (Table 3 and Figure 2). T. acidophilum XPD was shown to unwind a forked duplex, but to our knowledge its preference for that substrate compared with other partial duplex DNA molecules was not evaluated [22].…”
Section: Biochemistrymentioning
confidence: 99%